Ethnomathematics of Damar Kurung: A Local Cultural Contextualization Alternative in Mathematics Learning at Madrasah Ibtidaiyah Miftahul Ulum Kesamben Wetan Gresik - Anggita Pasha; Nadi Suprapto; Ari Metalin Ika Puspita (Program Studi PGMI, 2025)
Abstract Mathematics learning in elementary schools is often perceived as abstract and disconnected from students’ real-life experiences. This study introduces the local art of Damar Kurung from Gresik as an ethnomathematical medium to strengthen students’ understanding of plane geometry. This research employed a qualitative case study design conducted at Madrasah Ibtidaiyah Miftahul Ulum Kesamben Wetan Gresik. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that integrating Damar Kurung into mathematics learning enhances student engagement, spatial reasoning, and appreciation of local culture. Teachers became more creative in linking geometric concepts with cultural artifacts, resulting in a more meaningful and enjoyable learning process. Damar Kurung ethnomathematics serves as an effective alternative to connect mathematics with students’ cultural identity and daily life. This model not only improves cognitive understanding but also fosters cultural values, creativity, and pride in local heritage. Keywords: ethnomathematics, Damar Kurung, plane geometry, local culture, contextual learning Abstrak Pembelajaran matematika di sekolah dasar sering dianggap abstrak dan jauh dari kehidupan nyata siswa. Penelitian ini berupaya menghadirkan konteks budaya lokal Gresik melalui seni Damar Kurung sebagai media etnomatematika untuk memperkuat pemahaman konsep bangun datar. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus yang dilaksanakan di Madrasah Ibtidaiyah Miftahul Ulum Kesamben Wetan Gresik. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, kemudian dianalisis dengan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa integrasi Damar Kurung dalam pembelajaran matematika meningkatkan keterlibatan siswa, kemampuan berpikir spasial, dan apresiasi terhadap budaya lokal. Guru juga lebih kreatif dalam mengaitkan konsep geometri dengan artefak budaya, sehingga pembelajaran menjadi lebih kontekstual dan menyenangkan. Etnomatematika Damar Kurung menjadi alternatif efektif untuk menghubungkan matematika dengan kehidupan dan identitas budaya siswa. Model ini tidak hanya memperkuat pemahaman kognitif, tetapi juga menumbuhkan nilai-nilai budaya, kreativitas, dan rasa memiliki terhadap warisan lokal. Kata Kunci: etnomatematika, Damar Kurung, bangun datar, budaya lokal, pembelajaran kontekstua.